2019
DOI: 10.1109/comst.2018.2874356
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Limitations and Enhancements of the IPv6 Routing Protocol for Low-Power and Lossy Networks: A Focus on Core Operations

Abstract: Driven by the special requirements of the Lowpower and Lossy Networks (LLNs), the IPv6 Routing Protocol for LLNs (RPL) was standardized by the IETF some six years ago to tackle the routing issue in such networks. Since its introduction, however, numerous studies have pointed out that, in its current form, RPL suffers from issues that limit its efficiency and domain of applicability. Thus, several solutions have been proposed in the literature in an attempt to overcome these identified limitations. In this surv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(62 citation statements)
references
References 110 publications
(252 reference statements)
0
62
0
Order By: Relevance
“…The presented analysis and evaluation of RPL behavior are done while targeting only a single objective function. Moreover, the authors in Ghaleb et al addressed enhancements of RPL in three fields: routing maintenance, objective functions, and downward routing enhancements, while in Kamgueu et al, RPL enhancements addressed topology, security, and mobility.…”
Section: Related Workmentioning
confidence: 99%
“…The presented analysis and evaluation of RPL behavior are done while targeting only a single objective function. Moreover, the authors in Ghaleb et al addressed enhancements of RPL in three fields: routing maintenance, objective functions, and downward routing enhancements, while in Kamgueu et al, RPL enhancements addressed topology, security, and mobility.…”
Section: Related Workmentioning
confidence: 99%
“…RPL is an extended distance vector-based protocol for IoT. Routing limitations and challenges in sensor networks, as the most salient subset of IoT, distinguishes it from all other distributed systems [24]. Such limitations affect the whole design of wireless sensor networks, including various protocols and algorithms of other classifications of IoT.…”
Section: ) Cluster-based Mechanismsmentioning
confidence: 99%
“…RPL was standardized for 6LoWPAN networks bringing the concept of IoT into real life. Since then, many studies have evaluated the performance of RPL and they have suggested some improvements to potential shortcomings and open issues [13,14]. In the literature, many research works have carried out on various aspects of RPL based wireless sensor networks (WSNs), such as load balancing, energy conservation, QoS support, and protocol optimization [15].…”
Section: Related Workmentioning
confidence: 99%